2011
DOI: 10.1136/injuryprev-2011-040149
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the fireground: injuries in the fire service

Abstract: Background Although firefighting and emergency medical services are high-risk professions, few studies have identified the aetiology of injury in the fire service beyond the fireground. Methods Data were collected for work-related injuries in a medium-sized metropolitan fire department. In a descriptive study, the factors explored included the nature of injury, agent, mechanism, body location, environment, abbreviated injury scale (AIS), functional capacity index (FCI) and lost time status. Results From 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
118
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 26 publications
8
118
2
6
Order By: Relevance
“…About 1.2 million firefighters are among the occupational groups with high obesity prevalence in the US [Caban et al, 2005;Choi et al, 2011;Haddock et al, 2011;Gu et al, 2014] and are at high risk of on-duty cardiovascular disease (CVD) mortality [Kales et al, 2007;Geibe et al, 2008]. At the same time, they are also at higher risk for workrelated injuries [Poplin et al, 2012;Jahnke et al, 2013] also associated with obesity or aerobic fitness level [Kuehl et al, 2012;Jahnke et al, 2013;Poplin et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…About 1.2 million firefighters are among the occupational groups with high obesity prevalence in the US [Caban et al, 2005;Choi et al, 2011;Haddock et al, 2011;Gu et al, 2014] and are at high risk of on-duty cardiovascular disease (CVD) mortality [Kales et al, 2007;Geibe et al, 2008]. At the same time, they are also at higher risk for workrelated injuries [Poplin et al, 2012;Jahnke et al, 2013] also associated with obesity or aerobic fitness level [Kuehl et al, 2012;Jahnke et al, 2013;Poplin et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Examining American firefighters, Karter and Molis [10] have shown that strains, sprains and muscular pain accounted for the largest portion of injuries (51.4 %), whereas Poplin et al [11] found that 32.9 % of injuries were due to physical exercise, followed by patient transport (16.9 %), training drills (11.1 %) and fire ground operations (10.2 %). An analysis of the injury incidence by age groups [12] has revealed the lowest and less frequent values among firefighters aged 30-39 and the highest among those aged more than 50 years, whereas during compulsory physical training accidents were less frequent in the 40-49 age groups than others (age 20-29 and 50-59 years).…”
Section: Introductionmentioning
confidence: 99%
“…Male firefighters are among the top three occupational groups with the highest obesity prevalence in the USA (Caban et al 2005;Choi et al 2011;Haddock et al 2011). As a result, overweight and obesity is an important occupational health issue to be urgently addressed for the 1.1 million US firefighters ) who are at high risk of on-duty cardiovascular disease (CVD) mortality (Geibe et al 2008;Kales et al 2007) and musculoskeletal injuries Poplin et al 2012). …”
mentioning
confidence: 99%